S100A9 Tetramers, Which are Ligands of CD85j, Increase the Ability of MVAHIV-Primed NK Cells to Control HIV Infection - Moreno-Nieves, Uriel Y.; Didier, Céline; Lévy, Yves; Barré-Sinoussi, Françoise; Scott-Algara, Daniel; , ANRS HIV Vaccine Network (AHVN) (Frontiers in Immunology, 2015)
Natural Killer (NK) cells are the major antiviral effector population of the innate immune system. We previously found that S100A9 is a novel ligand of the receptor CD85j and that S100A9 tetramers enhance the anti-HIV activity of NK cells. Also, we found that DCs infected by the HIV vaccine candidate, MVAHIV, prime NK cells to specifically higher control HIV infection in autologous CD4+ T cells. In this study, we analyzed whether stimulation of NK cells by S100A9 tetramers prior the priming by MVAHIV-infected DCs modulates the subsequent anti-HIV activity of NK cells. We found that S100A9 tetramers activate NK cells and that DCs enhance the anti-HIV activity of NK cells. Interestingly, we observed that stimulation of NK cells by S100A9 tetramers, prior the priming, significantly increased the subsequent anti-HIV activity of NK cells; and that the enhanced anti-HIV activity was observed following different conditions of priming, including the MVAHIV-priming. As S100A9 tetramers alone directly increase the anti-HIV activity of NK cells and as this increased anti-HIV activity is also observed following the interaction of NK cells with MVAHIV-infected DCs, we propose S100A9 tetramers as potential adjuvants to stimulate the anti-HIV activity of NK cells.